Perjuangan wanita dalam aktivisme sosial dan nasionalisme di Tanah Melayu, 1929-1957 / Ruhana Padzil - Ruhana, Padzil (2017)
The central focus of this research is to highlight the history of women's activism before Malayan independence, between the years 1929-1957 using a feminist perspective. Historical research was adopted as the main approach in this study. Library and archival research was utilized for review and analysis of primary sources which range from documents, government reports, special reports, government files, interview transcripts, magazines, and newspapers. Interview method was also employed in this study. The main objective of this study was to reveal the development of feminist sentiments through social activism and nationalism in Malaya. The study also analyzed the struggle of women as labor against exploitation and discrimination which contributed to the rise of anti-colonial sentiments and nationalism. In addition, it also analyzed the participation of women in both the political right-wing and left-wing struggle against British colonial rule. An awareness that education is the key to creating a modern society, led these women activists to mobilize women to participate in social and political activism towards encouraging female education which was ideologicaly used to empower Malay women to discard practices that subordinated them which was also nationalist in sentiments. In addition, the study shows the emergence of feminist sentiments among women in Malaya before independence through social activism and nationalism which can be observed in the domains of journalism, creative writing in magazines and newspapers and in labor activism. The feminist sentiment can be discerned from the women’s movement’s call for female education and in the move to discard practices that subordinated women such as forced marriage, polygamy and etc. This study found that women activists used their identity as mothers and employed the maternal thinking approach to be involved in social and political activism. This strategy allowed for them to take on the responsibility as leaders and advocates for the community. Besides that it allowed them to negotiate with patriarchy for a more public presence in the political domain both formal and informal. Some women from the left wing political party had the confidence, courage and willingness to become militants in the fight against imperialism. Furthermore, Malay Chinese and Indian women struggled and fought against the injustice and exploitation of labor in Malaya which gave rise to anti-colonial sentiments. The labor movement in Malaya eventually led to the rise of labor power that ultimately contributed to the nationalist struggle in Malaya. In addition, the study found that women's involvement in social activism gave rise to the emergence of female leaders in both the right and left wing politics, who struggled for the independence of Malaya. The experiences and the voices of these women are included in this study. In addition, most women political activists assume their experiences as women, mothers and their marginalization in the domestic realm as a major impetus for their involvement in activism and politics to become agents of change in their society which contributed to their nationalist and anti-colonial actions for an independent Malaya.